The passion of al-Hallaj : Mystic and Martyr of Islam. - Massignon, Louis, 1883-1962 (Princeton University Press, 1994)
Abridged from the four-volume The Passion of al-Hallaj, one of the major works of Western orientalism, this book explores the life and teaching of a famous tenth-century Sufi mystic and martyr, and in so doing describes not only his experience but also the whole milieu of early Islamic civilization. Louis Massignon (1883-1962), France's most celebrated Islamic specialist in this century and a leading Catholic intellectual, wrote of a man who was for him a personal inspiration. From reviews of the four-volume translation:
Description based upon print version of record.
The Towns of Transoxiana (Mawaralnahr): Bukhara, Samarqand, Ush, Isfijab.
Keywords: Ḥallāj, al-Ḥusayn ibn Manṣūr, -- 858 or 859-922.; Ḥallāj, al-Ḥusayn ibn Manṣūr, -- 858 or 859-922; Sufis -- Biography.; Soufis -- Biographies.; Sufis; Biographies